The Pengaruh Rasio Kecukupan Modal, Resiko Kredit, Profitabilitas Dan Likuditas Terhadap Financial Distress Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016 – 2020 - Eddo Mochammad Kareem; Didit Supriyadi; Sri Suartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine and analyze the effect of financial performance in the form of banking ratios CAR, NPL, ROA, ROE and LDR on financial distress in banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample used in this study were 32 banking companies listed on the Indonesia Stock Exchange. The data analysis method used is descriptive statistical method and multiple linear regression method for panel data. The results of this study indicate that CAR, NPL, ROA, ROE and LDR simultaneously have a significant effect on Financial Distress. While partially CAR and ROA have a significant positive effect on Financial Distress in banking companies listed on the Indonesia Stock Exchange, while NPL, ROE and LDR have no effect on Financial Distress in banking companies listed on the Indonesia Stock Exchange 2016-2020. Keywords: CAR, NPL, ROA, ROE, LDR, Financial Distress